The Economic and Social Dimension of Innovative Approaches in Sustainable Agricultural Policies and the Role of Municipalities - Hakkı Mümün Ay; Adnan Söylemez; Nihal Güneş Ay (Turkish Journal of Agriculture: Food Science and Technology)
In recent years, intensive legal regulations aimed at the production of urban areas in Türkiye, the phenomenon of migration, the spread of higher education, abnormal cost increases in agricultural activities have accelerated urbanization. Parallel to the increase in the urban population, the food supply remains insufficient. The inability to increase the production of food products brings with it problems such as malnutrition, inflation, foreign trade deficit, food security. The natural areas harbored by rural and urban areas are shrinking and being destroyed by the pressure of rapid urbanization. In addition to the abandonment of rural areas, the food crisis that has arisen as a result of the intervention of the urbanization process in agricultural areas has increased the responsibility of the central government and municipalities. In order to meet the food needs of the population and implement sustainable agricultural policies, municipalities are taking different and innovative approaches. Municipalities are making direct and indirect attempts to provide people with cheap and reliable food. In this study, the activities carried out by the municipalities in Türkiye to support sustainable agriculture and their economic and social effects were examined.